PENGEMBANGAN MEDIA PEMBELAJARAN INOVATIF “PAPA MENDALANG” PADA PERKEMBANGAN AUD DI TK PANDU ILMI PERSADA - Estuhono Estuhono; Agus Saputra; Tesya Novita (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research is motivated by the importance of developing learning media that creates feelings of pleasure in the learning process, then it can stimulate students development. The purpose of this research is tosee children’s learning outcome aster using the innovative learning media “Papa Mendalang” The type of this research is a research and development. The type of development model in this research is Plomp Model. The Plomp Model consists of preliminary research, prototyping phase and assessment phase. The determine the feasbility of the learning media being development, an assessment was carried out by using validation, practicalities and effectiveness sheets. The result of the feasibility of innovative learning media “Papa Mendalang” on early childhood development carried out by three velidators got an average of 87,85 % with a very valid category. The results of the assessment of the implementation of the innovative learning media “Papa Mendalang” on early childhood development early childhood which was assessed by the class teacher had a score of 94,44% with a very practical category. Student learning outcomes after using the innovative learning media “Papa Mendalang” on early childhood development obtained a percentage of 92 % in the effective category (has appreared).